2003
DOI: 10.1080/10426500307946
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Structures, Metallotropic 1,2-Shifts and Prototropic 1,2-Shifts of Cyclopentadienyl(trimethyl)silane, -germane and -stannane

Abstract: Molecular structures, metallotropic and prototropic shifts of cyclopentadienyl(trimethyl)silane (1), cyclopentadienyl(trimethyl)germane (2), and cyclopentadienyl(trimethyl)stannane (3) were investigated using ab initio molecular orbital and the Becke, Lee, Yang, and Parr density functional (B3LYP) methods. The results show that the most stable structure of compounds 1-3 has the (CH 3 ) 3 M fragment in the allylic position. The energy barrier of metallotropic shifts in compound 1 is higher than in 2, and in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Based on the present results it can be concluded that allylic isomer is the most stable isomer among the mentioned compounds. In addition, it was indicated that prototropic shift is much slower than metallotropic shift 19 . The 1,2-shift and hydrogen migration mechanisms for the Co(CO) 3 and BH 2 were studied using B3LYP/6-311+G** and MP2/6-311+G** levels of theory for compounds 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the present results it can be concluded that allylic isomer is the most stable isomer among the mentioned compounds. In addition, it was indicated that prototropic shift is much slower than metallotropic shift 19 . The 1,2-shift and hydrogen migration mechanisms for the Co(CO) 3 and BH 2 were studied using B3LYP/6-311+G** and MP2/6-311+G** levels of theory for compounds 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the published literature B3LYP results showed the increasing applicability of density functional theory (DFT) as a successful computational method and now DFT methods are known as reliable approaches for determining activation barriers and molecular energies. 12,13,16,17…”
mentioning
confidence: 99%